The persuasion - Johansen, Iris (New York : Grand Central Publishing, 2020)
Eve Duncan and ex-Navy Seal Joe Quinn ask Seth Caleb to keep their daughter, Jane, safe. Jane's talent as an artist has brought her to the attention of a madman. As Jane and Seth chase down their blood-thirsty adversary, they finally commit to one another. As they face danger, one thing is made clear: it will take both of them working together to confront and defeat this evil.
Keywords: Duncan, Eve -- (Fictitious character) -- Fiction; Man woman relationships -- Fiction; Romance fiction; Thrillers (Fiction)